Designing ui/ux for "building house" application through users centered design method - Rayhan Alif Akbar; Dadang Setiawan; Dana S Kusumo (Jurnal Mantik, 2023)
House is the basic need for humans as a place to live or shelter, and it serves as a primary location for activities after being outside. As time passes and the population becomes more crowded, the need for housing also increases. Many people require housing, whether purchasing ready-made houses, building new ones, or renovating an old house. This research addresses these issues through application development that utilizes data from the surrounding environment.